Political philosophy of his holiness the XIV Dalai Lama: selected speeches and writings - Shiromany, A .A. (ed.) (New Delhi, 1998)
The decision to bring out a volume on the political philosophy of His Holiness the 14th Dalai Lama pleases me to no end. As the world we live in is fast moving into a period of extreme uncertainty and growing ambivalence, and as the 20th Century which was marked by a uncanny combination of scientific achievement and the realisation of "freedom" and "self-determination" by millions of people on the one hand and the outbreak of so much human suffering, violence and repression in national and international arena on the other, the time has come for not confining political philosophy to academic high towers and turn to the thinking and vision provided by men like Dalai Lama and Mahatma Gandhi, alongside of course the wisdom and deep experience that flow from the grassroots of diverse societies and civilizations. That the two are intimately related, that the vision and periodic calls for collective action proclaimed by the former flow from the felt needs and practical wisdom flowing from the latter, is powerfully portrayed in the collection of speeches and writings put together in this volume.
Keywords: India-Politics and government